Characterizations of Null Holomorphic Sectional Curvature of GCR-Lightlike Submanifolds of Indefinite Nearly Kähler Manifolds (Analysis in Theory and Applications, 2016)
We obtain the expressions for sectional curvature, holomorphic sectional curvature and holomorphic bisectional curvature of a GCR-lightlike submanifold of an indefinite nearly Kähler manifold and obtain characterization theorems for holomorphic sectional and holomorphic bisectional curvature. We also establish a condition for a GCR-lightlike submanifold of an indefinite complex space form to be a null holomorphically flat.
Keywords: Indefinite nearly Kähler manifold; GCR-lightlike submanifold; holomorphic sectional curvature; holomorphic bisectional curvature.